Dimensionality and psychometric analysis of DLQI in a Brazilian population - Jorge, Marilia F. S. [UNESP]; Sousa, Ticiane D. [UNESP]; Pollo, Camila F. [UNESP]; Paiva, Bianca S. R.; Ianhez, Mayra; Boza, Juliana C.; Meneguin, Silmara [UNESP]; Schmitt, Juliano V. [UNESP]; Nunes, Daniel Holthausen; Lastoria, Joel C. [UNESP]; Miot, Hélio A. [UNESP] (Springer Nature, 2020)
Background: The Dermatology Life Quality Index (DLQI) is the most commonly used instrument for clinical evaluation of the impact on health-related quality of life (HRQOL) in dermatological research protocols. The DLQI's classical psychometric properties have been considered adequate in validation studies from several countries. However, the structure of the DLQI is a matter of discussion, especially concerning the dimensionality and informative properties of its questions according to the item response theory (IRT). Methods: Pooled data from studies in Brazil that utilized the DLQI to assess HRQOL in 14 dermatoses were reanalyzed. Classical psychometrical analysis, dimensionality assessment through parallel analysis and IRT (Samejima's ordinal model) analysis were performed. Results: The sample consisted of 1286 patients with a mean age of 47 years (SD = 16), and the proportion of women was 59% (765). The DLQI scores ranged from 0 to 29, with a median (p25-p75) of 5 (2-11). All items indicated significant correlations with the total DLQI score (rho > 0.54). The Cronbach's alpha result was 0.90 (CI 95% 0.89-0.91). Parallel analysis indicated a unidimensional factor structure. According to IRT analysis, items q6 (sports) and q7 (work/study) exhibited insufficient fit to the model (p < 0.01), while the items that indicated the best discrimination and information functions were q2 (embarrassment), q3 (shopping/gardening), q4 (clothing) and q5 (social/leisure). The ordination of the scores was confirmed for all items. Most items revealed non-uniform behavior according to sex, age and type of disease. Conclusions: The DLQI exhibits adequate psychometric reliability and a unidimensional structure for assessing HRQOL in Brazilian dermatological patients. The DLQI's performance varies in the assessment of HRQOL in heterogeneous samples.
Keywords: Dermatology; Factor analysis; Health-related quality of life; Psychometrics; Questionnaires; Validity